A study of prevalence of Anisometropia and associated amblyopia in patients with refractive error - Priti Singh; Rashmi Kumar; Jyoti Gontia; Devendra pratap singh; S B Gupta (International Journal of Medical Research and Review, 2015)
Aims: The present study was planned to evaluate the prevalence of anisometropia in patients with refractive error, to compare the prevalence of different types of anisometropia and to study the prevalence of amblyopia in anisometropic patients.Material and Method: It was a cross sectional study in which 400 randomly selected patients were evaluated for anisometropia and also for anisometropic amblyopia. All patients underwent thorough ophthalmic examination including visual acuity testing, slit lamp examination and fundus examination. Later on the data was analysed statistically with different formulas like Chi square test, Fisher exact test etc.Results: The prevalence of anisometropia was found to be 16.5% in total 400 patients with refractive errors, out of which 57.5% were females and 42.5% were male patients. Prevalence was found maximum in 20-30 years age group (36.4%). Highest prevalence among various types of anisometropia was found of compound myopic anisometropia (37.9%).Conclusion: No gender difference was seen in prevalence of anisometropia. Prevalence of anisometropia significantly varied with different age groups. The prevalence of amblyopia in patients of anisometropia was found to be statistically significant (p value=.0001).